Animalkind : remarkable discoveries about animals and revolutionary new ways to show them compassion - Newkirk, Ingrid; Stone, Gene, 1951- (Simon & Schuster, 2020)
"From the co-founder and president of PETA, Ingrid Newkirk, and bestselling author Gene Stone comes Animalkind, a book that offers both a tour of the wonderful world of animals and a guide to simple ways in which we can reduce the harm we cause them in our everyday lives"--